2014
DOI: 10.1007/978-3-319-07635-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Web Based Health Care and Resources for Mental Health: Interface Design Considerations for People Experiencing Mental Illness

Abstract: A significant proportion of society experience mental illness, many of which uses the Web for advice and support relating to their illness. With a high proportion of society experiencing anxiety and depression, it is important that web designers are informed of specific requirements to ensure Websites are accessible, particularly those websites that provide support and advice for mental health. Anxiety and depression can affect cognitive functioning, which can then impact upon the accessibility of web based in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Nine of the included studies [ 30 - 33 , 35 , 37 - 39 , 42 ] originated in the United States, 2 studies [ 34 , 40 ] in the United Kingdom, one [ 41 ] in Austria, and another [ 36 ] in Sweden as summarized in Table 1 . Over 62% (10/16) of the included publications [ 32 - 34 , 37 , 38 , 42 ] were published within the last 5 years, and the earliest [ 35 ] was published in 1998.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine of the included studies [ 30 - 33 , 35 , 37 - 39 , 42 ] originated in the United States, 2 studies [ 34 , 40 ] in the United Kingdom, one [ 41 ] in Austria, and another [ 36 ] in Sweden as summarized in Table 1 . Over 62% (10/16) of the included publications [ 32 - 34 , 37 , 38 , 42 ] were published within the last 5 years, and the earliest [ 35 ] was published in 1998.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the included studies investigated the usability of Web-based resources [ 30 - 34 , 37 - 40 ] and multimedia tools [ 35 ]. One study focused on Internet use [ 41 ], one on the use of digital technologies [ 36 ], one on the development of a mobile phone system [ 30 ], and another on computer use [ 42 ] among PwMD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Good and Sambhanthan [11] reported several website elements that people with depression and anxiety identified as being accessibility issues: distracting design, confusing menu options, poor navigation, time limited response forms, information overload, non-perceivable icons, slow response in websites loading information, poor organisation and presentation complicated language, poor content filters, excessive advertisements, and complex purchasing processes. Ferron et al [12] and Rotondi et al [10] concluded that people with severe mental disorders require sites that explicitly state instructions for their use, feature a shallow hierarchy of pages, use clear and explicit labels, large navigational cues and pop-up menus to reduce clicking.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough keyword search of several databases (i.e., MEDLINE, PsycARTICLES, CINAHL, Library, Information Science and Technology Abstracts, Computers and Applied Sciences Complete, ACM Digital Library, SpringerLink, OpenGrey) for Web accessibility, mental disorders and related terms only returned 3 directly relevant results (i.e., [10][11][12] as discussed earlier).…”
Section: Introductionmentioning
confidence: 99%